EVALUASI PENERAPAN AKUNTANSI PIUTANG USAHA PADA USAHA MIKRO, KECIL DAN MENENGAH - Maylina Rahmad Eka Syahputri; Amrie Firmansyah (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2019)
This study aims to review the implementation of accounting policies that include account receivables management and its policies as well as internal controls applied in Micro, Small and Medium Enterprises. The object used in this research is PT. XYZ engaged in advertising services. The research method used in this study using qualitative methods. The study was conducted during the period of April-June 2018. Interviews with the informant were conducted during the second week and third week of April 2018. The selection of informant is based on knowledge capabilities related to the information in this study. The informant in this research is the staff of finance at PT. XYZ. This research concludes that PT. XYZ generally has good accounts receivable management because PT XYZ has a collection procedure of receivable to clients. However, PT. XYZ does not yet have an adequate account receivable management policy because of PT. XYZ does not have good credit standards and credit terms, but the collection policy is quite effective by the company. Furthermore, PT. XYZ, in general, has performed internal control over the accounts receivable fairly well.